Room temperature interdigitated electrode acetone sensor based on SnO2-rGO hybrid composite - Yan, L.Z. (Institute of Electrical and Electronics Engineers Inc., 2019)
Metal oxide especially SnO2 has been highly appreciated as one of excellent sensing materials used in the realm of gas monitoring due to itâs low cost of production, ease of fabrication and high portability. However, low sensitivity and high operating temperature limits applications of SnO2 especially in health sector. This paper demonstrated acetone gas sensor based on Tin dioxide (SnO2) and reduced graphene oxide (rGO) composite film which was fabricated on micrometer scaled interdigitated electrode through facile hydrothermal method. Therein, beforehand study of SnO2-rGO composites includes variable pressure field emission scanning electron microscope and Raman spectrometry to understand the morphology and material content. Overall, the SnO2 doped rGO hybrid composite shows better gas sensing properties at room temperature in terms of response, recovery and repeatability with regression R2 = 0.8661 over wide dynamic range from 10ppm to 500ppm acetone if compared with bare rGO, indicating SnO2 attached on rGO attributes to better carrier mobility and gas adsorption. Â© 2019 IEEE.